The Effect of Propolis Irrigation as an Adjunctive to Scaling and Root Surface Debridement on Periodontal Health Status, Glycemic Control and Biochemical Markers in Subjects with Type 2 Diabetes Mellitus and Chronic Periodontitis: A Randomized Clinical - Hozan Wrya Azeez (Erbil Dental Journal)
Background: Periodontitis is the inflammation of supporting tooth structures; it is one of the six complications of diabetes, Propolis a local delivery agent can be used as an adjunct to non-surgical periodontal therapy.